1975
DOI: 10.1172/jci108069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute unilateral renal denervation in the rat.

Abstract: A B S T R A C T Studies were undertaken to characterize the renal responses to acute unilateral renal denervation and the mechanisms involved in these responses. Denervation was produced in anesthetized nondiuretic rats by application of phenol to the left renal artery. Studies were also performed in sham-denervated nondiuretic rats. Whole kidney and individual nephron studies were performed before and after denervation or sham denervation. Denervation increased urine volume from the left kidney to about twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(110 citation statements)
references
References 31 publications
8
100
1
1
Order By: Relevance
“…Animals were anaesthetized with methohexital (75 mg/kg i.p.) and denervated according to the method of Bello-Reuss et al [3]. The abdominal wall was opened along the midline and the left renal artery and vein were exposed by carefully retracting the adipose tissue and the peritoneum.…”
Section: Renal Denervationmentioning
confidence: 99%
“…Animals were anaesthetized with methohexital (75 mg/kg i.p.) and denervated according to the method of Bello-Reuss et al [3]. The abdominal wall was opened along the midline and the left renal artery and vein were exposed by carefully retracting the adipose tissue and the peritoneum.…”
Section: Renal Denervationmentioning
confidence: 99%
“…Conversely, removal of the renal nerve influence by acute denervation of the kidney is associated with increased urine flow and sodium excretion (5,6). These phenomena have been attributed by many investigators to reflect a direct influence of renal nerves on the tubule reabsorption processes.…”
Section: Introductionmentioning
confidence: 99%
“…Bello-Reuss et al (6,19) reported that in anesthetized rats renal nerve stimulation produced an increase in sodium reabsorption which occurred in the proximal convoluted tubule in the absence of changes in GFR or renal blood flow and that renal denervation induced a marked increase in urinary sodium and water excretion independent of changes in GFR or renal blood flow. In contrast to the latter results, renal denervation per se did not alter urinary sodium and water excretion in SHRSP and renal sympathectomy increased GFR in SHRSP-AC.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be blocked by adrenolytic drugs (4,5). When renal denervation was produced in anesthetized rats by application of phenol to the renal artery, urinary sodium excretion increased approximately five to six-fold without changes in renal hemodynamics (6).…”
mentioning
confidence: 99%